2008
DOI: 10.1002/prot.21985
|View full text |Cite
|
Sign up to set email alerts
|

Compact dimension of denatured states of staphylococcal nuclease

Abstract: Fluorescence and circular dichroism stopped-flow have been widely used to determine the kinetics of protein folding including folding rates and possible folding pathways. Yet, these measurements are not able to provide spatial information of protein folding/unfolding. Especially, conformations of denatured states cannot be elaborated in detail. In this study, we apply the method of fluorescence energy transfer with a stopped-flow technique to study global structural changes of the staphylococcal nuclease (SNas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 48 publications
1
2
0
Order By: Relevance
“…With the increase of GdmCl concentration, ⟨ E ⟩ of the non-native state of SNase exhibited a gradual decrease, indicating the expansion of the denatured state. Hence, our results of single molecule measurements showed that the equilibrium denaturation of SNase populated at least variable denatured states, the native state, and the possible intermediate, which agrees with recently reported kinetic results …”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…With the increase of GdmCl concentration, ⟨ E ⟩ of the non-native state of SNase exhibited a gradual decrease, indicating the expansion of the denatured state. Hence, our results of single molecule measurements showed that the equilibrium denaturation of SNase populated at least variable denatured states, the native state, and the possible intermediate, which agrees with recently reported kinetic results …”
Section: Discussionsupporting
confidence: 93%
“…The extrapolated value for K28C/H124C was a little higher than the respective ⟨ r 2 ⟩ 1/2 of the native state calculated directly from the experimentally determined ⟨ E ⟩ (37 Å for K28C/H124C and 38 Å for K28C/K97C), differing from that of K28C/K97C which is close to the native value. Also, in the same way, the R g of the non-native state extrapolated to native condition is 24 Å for K28C/K97C and 21 Å for K28C/H124C, which are both larger than 15.6 Å for the folded state reported by SAXS . In the calculation of R g , dye-linkers were considered to be equivalent to an additional 6 amino acid residues, and the Gaussian chain model according to Flory scaling law, R g = [149/( n + 6)] 1/2 (⟨ r 2 ⟩/6) 1/2 , was applied.…”
Section: Resultsmentioning
confidence: 99%
“…The dimension of the denatured states of SNase and some of its mutants is compact, no matter by acid or GdmCl denaturation. 22) The structure of WT SNase has been solved by both X-ray crystallography and nuclear magnetic resonance. Here we use the structure file 1EY0 for the analysis.…”
Section: Staphylococcal Nucleasementioning
confidence: 99%